Decoding Chemical Profiles, Biological Functions, and Medicinal Properties of Liquidambar orientalis Extracts Through Molecular Modeling and Bioinformatic Methods - Mehmet Cengiz Baloglu; Lutfiye Yildiz Ozer; Buket Pirci; Yasemin Celik Altunoglu; Sanam Iram Soomro; Gokhan Zengin; Mehmet Veysi Cetiz; Simone Carradori; Zoltán Cziáky; József Jekő (Food Frontiers)
ABSTRACT Liquidambar orientalis, the Anatolian sweetgum tree, is a relict and endemic species in Southwestern Turkey, traditionally used for therapeutic purposes. Our study comprehensively evaluated the therapeutic potential of L. orientalis extracts from its aerial parts to maximize bioactive compound extraction using methanol, ethyl acetate, and water as solvents. The methanolic extract exhibited the highest phenolic (73.04 ± 3.94 mg gallic acid equivalent [GAE]/g) and flavonoid content (48.86 ± 0.76 mg rutin equivalent [RE]/g), demonstrating superior antioxidant activity in 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) (256.61 ± 1.70 mg Trolox equivalent [TE]/g), 2,2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) (308.41 ± 3.14 mg TE/g), and cupric ion–reducing antioxidant capacity (CUPRAC) (411.13 ± 8.48 mg TE/g) assays. It also showed significant enzyme inhibition for acetylcholinesterase (4.43 ± 0.09 mg galanthamine equivalent [GALAE]/g), tyrosinase (149.16 ± 1.14 mg kojic acid equivalent [KAE]/g), amylase (0.93 ± 0.02 mmol acarbose equivalent [ACAE]/g), and glucosidase (1.60 ± 0.01 mmol ACAE/g), suggesting potential applications in neurodegenerative disease management, skincare, and diabetes treatment. Furthermore, methanol and water extracts displayed promising antimicrobial activity due to phenolic compounds such as chlorogenic acid and methyl‐3‐O‐caffeoyl quinate. The methanolic extract exhibited potent anticancer effects against lung cancer (A549) cells, with significant reductions in cell viability and induction of autophagy. The aqueous extract showed remarkable efficacy against prostate cancer (PC3) cells, modulating apoptosis markers. Breast cancer cells (MDA‐MB‐231) exhibited differential responses, with ethyl acetate extract promoting apoptosis and water extract–enhancing autophagy. Furthermore, molecular docking and dynamics simulations provided additional evidence supporting the therapeutic potential of key phytochemicals from L. orientalis, particularly afzelin and epigallocatechin, against cancer‐related targets and bacterial enzymes. Overall, this study fills a gap in understanding the enzyme inhibitory and diverse anticancer effects of L. orientalis extracts, highlighting its potential multi‐targeted therapeutic applications, particularly in cancer therapy.